Students' Perceptions of Bilingual Instruction (English-Indonesian) in Teaching Speaking at Class XII SMA Gunung Sari, Makassar - Fitrianti (Lingedu: Journal of Linguistics and Education, 2025)
ABSTRACT This research investigates students' perceptions of the use of bilingual instruction (English-Indonesian) in teaching speaking at Class XII SMA Gunung Sari, Makassar. The study also examines the benefits of bilingual instruction in enhancing students' understanding and participation in English lessons. A descriptive research method was employed, using a questionnaire administered to 30 students. The findings reveal that most students have a positive attitude toward bilingual instruction, recognizing its benefits in facilitating comprehension, vocabulary acquisition, and speaking skills